Diagnostic Value of Umbilical Artery Systolic/Diastolic Ratio and Amniotic Fluid Index for the Prediction of Respiratory Distress Syndrome among Term Pregnancies: A Cross-Sectional Validation Study: UA S/D Ratio and AFI: Respiratory Distress Syndrome among Term Pregnancies - Khawar, Alesha; Saeed, Muhammad; Hussain, Naveed; Sharif, Sana; Mehar, Fareeha Khalid; Ghani, Naureen (Pakistan Journal of Health Sciences, 2026)
The introduction of UA S/D ratio monitoring into the routine antenatal Doppler monitoring can improve the early detection of the at-risk baby and optimize the perinatal care. Objectives: To evaluate the diagnostic accuracy of umbilical artery (UA) systolic/diastolic (S/D) ratio, and amniotic fluid index (AFI) in term pregnancies for the prediction of RDS, keeping postnatal findings as the gold standard. Methods: This cross-sectional validation study was carried out at Department of Diagnostic Radiology, Pakistan Navy Ship Hafeez Hospital, Islamabad, from November 2024 to June 2025. There were 594 enrolled term pregnant women with term pregnancies. The obstetric ultrasound with color Doppler was performed to measure the umbilical artery S/D ratio and AFI. S/D ratio was declared positive when its >3, and AFI positive when it was < 8 cm. Neonates were followed 72 hours after birth, and the RDS diagnosis was confirmed by clinical and radiological means. Data were evaluated with SPSS version 25.0, and diagnostic indices were calculated. Results: The overall prevalence of RDS was 12.6%. For the umbilical artery S/D ratio, sensitivity and specificity were 77.3% and 88.1%, respectively. While for AFI, sensitivity and specificity were 64.0% and 75.7%, respectively. Conclusions: The Umbilical artery S/D ratio is a better and more reliable ultrasound parameter than AFI in predicting postnatal RDS in term pregnancies, as the AUC for the UA S/D ratio was found to be 0.840, which reflects its optimal performance, while the AUC for AFI was found to be 0.305, which shows its poor discriminative ability.